THE IMPACT OF THE CARBONETIC FOUNDATION MANGROVE RESTORATION PROGRAMME ON THE INCOME OF COASTAL COMMUNITIES IN DOMPAK ISLAND - Sihombing, Daud Crisvo; Khairunnisa, Khairunnisa; Zen, Linda Waty (Politeknik Kelautan dan Perikanan Dumai, 2024)
Dompak Island is a mangrove area that has great potential in the Tanjungpinang urban area. However, the area of mangrove land decreases every year due to excessive mangrove logging. So a mangrove restoration program was formed by the CarboEthics Foundation. Apart from having an ecological impact, it also has an economic impact on society. The aim of the research is to estimate community income before and after the mangrove restoration program on Dompak Island. This research was conducted in March-April 2024 in the Tanjung Siambang Tourism Village which is located on Dompa Island. The research uses data analysis by calculating income. The results of the research are that the average income for the restoration worker program is IDR 52,356,333. The percentage change in income is an average of 60%.